2009
DOI: 10.1002/mame.200900031
|View full text |Cite
|
Sign up to set email alerts
|

Spheroidal Nanoparticles in Epoxide‐Based Adhesives

Abstract: Epoxy resins are a very important class of structural adhesives and property improvements are constantly being sought. As the interaction between the polymer and the surface of nanoparticles is nothing other than adhesion, there is obvious scope for property improvements by adding nanoparticles having tailored surfaces. Particles agglomeration, surface chemistry, and the thickness and composition of the particle‐polymer interphase are crucial for the resulting material properties. Also, the simultaneous use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…[1] To influence other important properties such as cohesive strength, viscosity and softening temperature further modifications to the adhesive are often necessary. [2] . Recent studies have considered the effects of inorganic fillers on the properties of adhesives.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[1] To influence other important properties such as cohesive strength, viscosity and softening temperature further modifications to the adhesive are often necessary. [2] . Recent studies have considered the effects of inorganic fillers on the properties of adhesives.…”
Section: Introductionmentioning
confidence: 95%
“…Inserting carbon nanotubes into adhesives has thereby improved mechanical and electrical properties of the adhesives. [2,10,11,22,27,28] The aim of this study was the enhancement of the properties of a commercially used …”
Section: Introductionmentioning
confidence: 99%
“…The involvement of a curing process during attachment indicates that a chemical interaction between the nanoparticles and the adhesive is most likely responsible for generating the high strength of this adhesive. The addition of nanoparticles to polymer epoxies and adhesives has previously been shown to increase the adhesion strength of adhesives, only when the nanoparticles interact with the polymer matrix [110][111][112][113][114][115]. In cases where the nanoparticles do not react with the polymer they may still increase the mechanical properties of the polymers by serving as fillers within the matrix, but do not increase adhesion strength [116,117].…”
Section: English Ivymentioning
confidence: 95%
“…[14,15] There are not much scientific researches that analyze the viability for the use of nano-reinforced polymers as adhesives. Most of the publications about nano-reinforced adhesives focus on the reinforcement of epoxy adhesives [16][17][18] and they revealed that the addition of small amounts of nanoparticles to epoxy adhesives can improve the mechanical resistance of structural joints. [2,19,20] The enhancement of the mechanical performance of the epoxy adhesives can directly be related to the improved shear strength of nano-reinforced joints.…”
Section: Introductionmentioning
confidence: 99%